Adult Wilms’ Tumor: A Rare Case Report - Gates Cook; Kelly Caldwell; Laura Adhikari; Sanjay Patel (Journal of Urological Surgery, 2018)

(untitled)
Wilms’ tumor is one of the most common intraabdominal malignancies among children and treatment protocols have been well studied in this population. The clinical presentation differs between the pediatric and adult populations with adults presenting similar to patients with renal cell carcinoma. Diagnosis is usually made by surgical pathology as imaging cannot differentiate between Wilms’ tumor and other kidney pathologies. In addition to surgical excision, treatment includes systemic chemotherapy and/or radiation. In this case report, we present a patient who underwent successful surgical resection of a 29x24x25 cm right-sided Wilms’ tumor with subsequent chemotherapy and radiation.